A new species of Frontodendroidopsis (Coleoptera: Pyrochroidae: Pyrochroinae) from China, with a key to males of the three species - Young, Daniel K. (Zootaxa, 2017)
Frontodendroidopsis pennyi, a new species of fire-colored beetle, is described from two males taken along the South Fork of Yamu He, 1.3 km east of Lao Shibali, northwestern Yunnan Province, China at an elevation of 2250 meters. This is the third described Frontodendroidopsis, the others being F. gibbiceps Young, also from China and the Japanese F. ocularis (Lewis). A similar cranial modification, large compound eyes, and strongly pectinate antennae place the new species in Frontodendroidopsis, although the antennal pedicel is shorter. Unlike F. gibbiceps the antennal insertions are not swollen and the frons is not carinate. The conspicuously emarginate fifth ventrite exhibited by males F. pennyi and F. gibbiceps distinguishes both of these species from F. ocularis.